PENGEMBANGAN BAHAN AJAR MATERI IPS MODEL RECE (REFLECTIVE, EFFECTIVE, COLLABORATIVE, ELABORATIVE) UNTUK MEMBANGUN KEMAMPUAN LITERASI SOSIAL BERBASIS KEARIFAN LOKAL SISWA SEKOLAH DASAR - Indah Wardatussaidah; Taofik; Yustia Suntari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Success in a learning process cannot be separated from the existence of adequate resources, one of which is the source of teaching materials. Of all the existing teaching materials, especially in elementary schools, not all teaching materials are able to synergize between teachers and students. Problems arise when the existing teaching material resources are not serialized properly and correctly. The objectives of this study include (1) theoretically reviewing the concept of RECE model social studies teaching materials (2) analyzing field needs related to appropriate teaching materials, (3) developing a draft concept of RECE model social studies teaching materials (4) validating the concept of RECE model social studies teaching materials based on social literacy and local wisdom (5) finalizing the product concept of RECE model social studies teaching materials based on social literacy and local wisdom (6) disseminating the concept of teaching materials. The research method that will be used in this study is the research and development method of the 4D Thiagarajan RnD model. The average percentage results from the material, language and media experts as a whole are 86.2% and can be categorized as a very feasible product, which means the RECE teaching model is suitable for use. Then in the one to one trial, the final recapitulation of the average value was 83% and was categorized as valid, then in the small group test with an average result of 86% and was categorized as very valid and finally the field test with an average result of 90.3% with a very valid category and suitable for use without the need for revision. It can be concluded that the product developed in the form of RECE model teaching materials is a very feasible product and can be used as teaching materials in social studies subjects in elementary schools.